PENGARUH RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, DAN CAPITAL TERHADAP RETURN SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Nopi Astuti, 12.05.52.0212; Aini, Nur (Students Journal of Accounting and Banking, 2016)
RGEC method, which stands for Risk Profile, Good Corporate Governance, Earnings and Capital is a guideline bank rating newest Per January 2012. The problem in this study is whether the Risk Profile, Good Corporate Governance, Earnings and Capital effect on stock returns bank company in BEI. The purpose of this study was to analyze the impact Risk Profile, Good Corporate Governance, Earnings and Capital on stock returns of banks in BEI. The population in this study are all the banks listed on the Indonesia Stock Exchange period 2012 - 2014. The research sample is determined by purposive sampling is a sampling technique by using certain considerations or criteria. The sample in this study as many as 28 companies. This study uses multiple regression analysis. The results of this study that partially (1) Non performing loans (NPL) have a negative impact and not statistically significant to share return; (2) Good Corporate Governance (GCG) has a positive influence and not statistically significant to share return; (3) Return on Assets (ROA) have a negative impact and not statistically significant to share return; and (4) Capital Adequacy Ratio (CAR) have a positive effect and is statistically significant to stock return. Â Keywords: Non-Performing Loans, Good Corporate Governance, Return on Assets, Capital Adequacy Ratio and Stock Return